Comparative biology and growth rate of the two predatory mites, Cydnoseius negevi and Neoseiulus californicus (Acari: Phytoseiidae), reared on two pea cultivars - Amira Abdel-Khalek; Gomaa Abou-Elella; Elsayed El-Saiedy (Persian Journal of Acarology)
Laboratory experiments were conducted to investigate the influence of two pea cultivars, regular and sweet as substrates on biological aspects and life table analysis of two phytoseiid species, Cydnoseius negevi (Swirski & Amitai) and Neoseiulus californicus (McGregor) fed on nymphs of Tetranychus urticae Koch under laboratory conditions of 27 ± 1 ℃, 70–80 % RH and 16L:8D h photoperiod. The development was faster and reproduction of N. californicus was higher compared with C. negevi. The predatory mite N. californicus showed the highest fecundity when reared on sweet pea cultivar, while C. negevi exhibited the lowest fecundity when reared on regular pea cultivar. Rearing C. negevi on the two pea cultivars led to the greatest female longevity than that of N. californicus. Feeding capacity of females during oviposition period was the highest for N. californicus on sweet pea, but it was the lowest for C. negevi on regular pea cultivar. Life table analysis showed that the shortest mean generation time (T) for N. californicus (13.01 days) compared with C. negevi (14.65 days) on sweet pea cultivar. Also, the intrinsic rate of increase (rm) of N. californicus was 0.29 female/female/day, but the rm value was 0.24 female/female/day for C. negevi on sweet pea substrate. Therefore, it can be concluded that the two predatory mites, C. negevi and N. californicus, are efficient biological control agents against T. urticae on the two pea cultivars.